The Significance of Career for Individuals - Myszka-Strychalska, Lucyna (Kultura-Społeczeństwo-Edukacja, 2019)
Professional career has become an increasingly frequently chosen subject of theoretical research based on numerous sciences, such as psychology, sociology, economics, pedagogy, and management. Constantly emerging, new theories of professional development provide a new perspective on this issue. A plethora of contemporary transformations obliges an individual to take responsibility for his or her own professional biography. If every person carries out a career, regardless of its quality, and if that career lasts for the person’s whole lifetime, both throughout the period of professional activity and the time of preparation preceding it, one can presume that the choice of career requires reflection and in-depth conceptual considerations, which proves its significance for the subject.